New Insights into SnO2/Al2O3, Ni/Al2O3, and SnO2/Ni/Al2O3 Composite Films for CO Adsorption: Building a Bridge between Microstructures and Adsorption Properties - Mozaffari, Nastaran; Solaymani, Shahram; Achour, Amine; Kulesza, Slawomir; Bramowicz, Miroslaw; Nezafat, Negin Beryani; Ţălu, Ştefan; Mozaffari, Niloofar; Rezaee, Sahar (Journal of physical chemistry. C, 2020)
As the environment and the human body face harmful effects of toxic gases such as carbon monoxide (CO), many research efforts have been directed toward elimination of these species through various adsorption processes. Unique properties of γ-Al2O3 in CO capture have led us to prepare SnO2/Al2O3, Ni/Al2O3, and SnO2/Ni/Al2O3 composite nanocrystalline films using the roll-coating method. The crystalline structure and morphology of the coatings were investigated using X-ray diffraction and field-emission scanning electron microscopy, respectively. The performed analyses revealed the complex microstructure of the coatings composed of fine grains and well-dispersed nanoparticles that aggregated to form larger well-developed clusters. Following this, adsorption characteristics of the samples were measured using the KIMO KIGAZ 210 continuous flow gas analyzer. Finally, the kinetics of the CO adsorption process was studied using various diffusion models: pseudo-first-order, pseudo-second-order, and intraparticle.